Awareness of Pregnant Women Regarding Pregnancy and Safe Delivery in Selected Rural Area (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Objective: This cross sectional descriptive study was conducted to explore awareness level of pregnant women regarding pregnancy and safe delivery in selected rural area.Methodology: This community based cross sectional descriptive study was carried out at Ullapara Upazila, Sirajgonj District among 120 pregnant women in a rural community. Non probability sampling technique and pretested semistructured questionnaire was used to collect data. Results: Majority of the respondents (65 %) were between 20-34 years of age group. Most of the respondents were housewives (85%). Majority (65%) of the respondents received antenatal care, and among them only 5% respondents received complete antenatal care and 25% received postnatal care. Majority (75%) of the respondents had not received postnatal care (PNC). Majority (85 %) of the respondent planning their delivery in the home and 15% respondent planning their delivery in the delivery center. About 50% of the respondents got information regarding pregnancy and delivery care through health workers. Besides 35% of respondents got information through doctor. Moreover 50% participants knew about the obligatory indications and 50% did not. Sixty percent participants did not know follow-up regarding PNC. Only 25% received PNC. Besides 60% participants did not know about warning sign during delivery while 40% faced complications during their last delivery. About 55% participants did not have knowledge regarding baby care. Moreover 55% participants did not take contraceptive method after their delivery. Conclusion & Recommendation: Attention should be given to improve education level and employment status of the people, as well as supply of all of the necessary equipment and EOC should also be incorporated. Regular awareness program may have to be conducted; Government and non-government organizations should be integrated more in pregnancy issue and post-delivery care. Development and strengthen behavioral change of communications and activities in order to create awareness about pregnant women are also important indeed.DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21059